The importance of mentorship and the impact of stress when measuring program satisfaction for students of color in psychology graduate programs - Curry, Ashley (2022)
Students of color in graduate degree programs experience stress at a level that exceeds their peers. Not only do students experience common graduate stressors, but they also experience racial stressors such as microaggressions. They are also less likely to experience quality mentorship, which can provide them with the support required to be successful throughout their graduate school experience. The purpose of this study was to evaluate the stress levels as well as program satisfaction of psychology graduate students of color in relation to their experiences of quality mentorship. Survey data was collected to reveal perceptions of quality mentorship, reported stress levels including the experience of racial stressors, and overall program satisfaction. Participants were recruited from social media graduate student groups which contained students who were currently or previously enrolled in Psychology graduate programs. 41 participants participated in the study (African American/Black: 23, Asian: 2, Multicultural: 3, 17: Latino, and Other: 4) from Clinical, School, and “Other” Psychology programs. Multilinear regression analysis and Pearson's Correlations were used to evaluate program experiences of students in Psychology graduate programs. This study is considered underpowered, limitations and recommendations for future research have been included in this literature.